The role of social media in sustainable marketing communication : a study on airline industry on Instagram - Lehtonen, Siru (My University, 2021)
The purpose of this thesis was to study how sustainability is mediated in organisations’ marketing communication. The purpose was divided into four research questions: what is sustainability and sustainable marketing communication, what is the role of social media in sustainable marketing communication, what aspects of sustainability airline industry communicates on Instagram and what communication strategy the airline industry utilises the most on Instagram. Sustainable marketing communication was discussed through sustainable development, strategic corporate social responsibility and triple bottom line. The thesis also studied the support social media gives to sustainable marketing communication. The thesis processed new information utilising previous studies on sustainability and social media. The empirical material based on secondary data (N=204) was collected from Instagram and analysed using quantitative content analysis and the code sheet created for this study. The results were gathered, and conclusions presented by combining previous studies and the empirical material of this study. According to the results, 11% of the airlines’ marketing communication on Instagram is sustainable marketing communication. The most communicated dimension of sustainability was social, and elements were employee welfare, safety, health care and equal rights. The results also showed that two thirds of sustainability posts on Instagram implemented informing strategy. This is conflicted with the engaging nature of social media. In addition to managerial implications, this study also offers significant new information on sustainable marketing communication on social media. The thesis was able to address research gaps in previous studies on the role of Instagram in sustainable marketing communication.
Keywords: sustainability, sustainable marketing communication, social media, quantitative content analysis, Instagram